2015
DOI: 10.1038/mi.2014.119
|View full text |Cite
|
Sign up to set email alerts
|

Commensal enteric bacteria lipopolysaccharide impairs host defense against disseminated Candida albicans fungal infection

Abstract: Commensal enteric bacteria maintain systemic immune responsiveness that protects against disseminated or localized infection in extra-intestinal tissues caused by pathogenic microbes. However, since shifts in infection susceptibility after commensal bacteria eradication have primarily been probed using viruses, the broader applicability to other pathogen types remains undefined. In sharp contrast to diminished antiviral immunity, we show commensal bacteria eradication bolsters protection against disseminated C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
(85 reference statements)
1
5
1
Order By: Relevance
“…Therefore, the immune communication is essential for intestinal microbiota to protect against invasive candidiasis. A previous study has indicated that commensal bacteria eradication enhanced protection against disseminated C. albicans infection [38], which is in contrast with our present work. The following two points may explain this difference.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Therefore, the immune communication is essential for intestinal microbiota to protect against invasive candidiasis. A previous study has indicated that commensal bacteria eradication enhanced protection against disseminated C. albicans infection [38], which is in contrast with our present work. The following two points may explain this difference.…”
Section: Discussioncontrasting
confidence: 99%
“…To investigate the role of the intestinal microbiota in invasive candidiasis, we first treated SPF C57BL/6 mice with antibiotic cocktail for 2-3 weeks and then these mice were intravenously challenged with C. albicans. A previous study has confirmed the validity of this approach to deplete intestinal microbiota [38]. In parallel, CNV mice were challenged with an equivalent amount of candida yeasts.…”
Section: Depletion Of Intestinal Microbiota Decreased Survival In a Mmentioning
confidence: 67%
See 1 more Smart Citation
“…This ability of fungi to rapidly accumulate after antibiotic induced eradication of intestinal bacteria was exploited to investigate whether commensal fungi – in isolation – can functionally recapitulate the protective benefits of enteric bacteria. Supplementing the drinking water with a previously described cocktail of broad-spectrum antibiotics efficiently eliminates recoverable anerobic and aerobic bacteria from the feces of mice housed in our specific pathogen free facility (Figure 1A) (Abt et al, 2012; Jiang et al, 2015). 16S rDNA copies were also sharply reduced (>400-fold) in the feces of antibiotic treated compared with control mice (Figure 1B), in agreement with prior studies demonstrating commercial rodent chow subsequently becomes the major contributor and source of residual bacterial 16S rDNA in mice receiving this antibiotic cocktail (Hill et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…This analysis showed sharply reduced susceptibility to systemic invasive infection conferred by intestinal colonization. Mice with commensal C. albicans had improved survival following intravenous infection with a lethal dosage of virulent strain SC5314 for immune competent mice (Jiang et al, 2015) and >100-fold reduced fungal burden in the kidneys compared with control mice maintained on ampicillin-supplemented drinking water (Figure 2A). To confirm that C. albicans in the target tissue of colonized mice directly reflects reduced susceptibility to intravenous infection, as opposed to dissemination from intestinal tissue, we took advantage of GFP expression by recombinant virulent C. albicans strains (Igya ´rto ´et al, 2011) allowing oral inoculation and subsequent intravenous challenge by unique isogenic strains (Figure 2B).…”
Section: Albicans Intestinal Colonization Protects Againstmentioning
confidence: 99%